Pengaruh Digital Public Relations terhadap Citra Merek Dove pada Kampanye RealBeauty - Arvel Naswan Hafizh; Muhammad Aprian Nazarudin; Ridho Yazhid; Sadiyah El Adawiyah (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2026)
Development of digital media has driven significant changes in public relations practices, particularly through the implementation of Digital Public Relations (Digital PR) as an organizational communication strategy. Digital PR allows companies to build two-way relationships with the public and shape brand image in a more interactive and sustainable manner. This study aims to analyze the influence of Digital Public Relations on Dove's brand image in the #RealBeauty campaign. The study uses a quantitative approach with a survey method involving 100 social media users who are aware of the #RealBeauty campaign. Data were collected through a Likert-scale questionnaire and analyzed using simple linear regression. The results of the study show that Digital Public Relations has a significant effect on Dove's brand image. Digital PR elements such as the quality of digital content, interactivity, message credibility, and value consistency have been proven to contribute to shaping positive consumer perceptions. This study affirms the strategic role of Digital PR in building a brand image based on social values in the digital era.